2011
DOI: 10.1073/pnas.1101039108
|View full text |Cite
|
Sign up to set email alerts
|

Fusion-activated Ca 2+ entry via vesicular P2X 4 receptors promotes fusion pore opening and exocytotic content release in pneumocytes

Abstract: Ca2+ is considered a key element in multiple steps during regulated exocytosis. During the postfusion phase, an elevated cytoplasmic Ca 2+ concentration ([Ca 2+ ]) c leads to fusion pore dilation. In neurons and neuroendocrine cells, this results from activation of voltage-gated Ca 2+ channels in the plasma membrane. However, these channels are activated in the prefusion stage, and little is known about Ca 2+ entry mechanisms during the postfusion stage. This may be particularly important for slow and nonexc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
136
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(147 citation statements)
references
References 60 publications
8
136
1
2
Order By: Relevance
“…1d), is in agreement with previous studies on other secretory cells, where very low amounts of the transcripts were detected (El-Kholy et al, 2007). Similarly, the subcellular localization of HCN channels in lactotrophs is consistent with previous findings (Noam et al, 2010;Fig. 1).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…1d), is in agreement with previous studies on other secretory cells, where very low amounts of the transcripts were detected (El-Kholy et al, 2007). Similarly, the subcellular localization of HCN channels in lactotrophs is consistent with previous findings (Noam et al, 2010;Fig. 1).…”
Section: Discussionsupporting
confidence: 81%
“…It has recently been shown that vesicular calcium channels regulate exocytosis by facilitating calcium entry through the fusion pore. This generates microdomains of increased [Ca 2ϩ ] i around the fused vesicles, which leads to the expansion of the fusion pore (Miklavc et al, 2011). Previous studies on lactotrophs showed a strong correlation between an increase in [Ca 2ϩ ] i and an increase exocytic activity (Vardjan et al, 2007;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can involve regulating the size of the initial fusion pore or fusion pore dilation (Albillos et al, 1997;Babich et al, 2008;Obermüller et al, 2005;Perrais et al, 2004;Tsuboi et al, 2004) or active extrusion of vesicle cargos. In ATII cells, fusion pores do expand in a Ca 2+ -dependent manner (Haller et al, 2001a;Miklavc et al, 2011), with most LBs exhibiting relatively large fusion pores that are stable for long periods (Haller et al, 2001a). This is in line with recent findings that fusion pores are the subjects of stabilization and that stable fusion pore diameters depend on vesicle sizes (Jorgačevski et al, 2010).…”
Section: Discussionsupporting
confidence: 76%
“…At the beginning of the experiment, cells were stimulated with 100 mM ATP, a potent agonist for LB fusion and surfactant secretion . LB fusions with the PM were indicated by rapid decay of Lysotracker Red (LTR) fluorescence in fused vesicles (Haller et al, 2001a;Miklavc et al, 2011) (see also Fig. 1).…”
Section: Actin Coating Of Fused Lbs Is Essential For Surfactant Expulmentioning
confidence: 99%